Implementation of Distribution and Determination of Village Funds (Case Study in Syamtalira Bayu, Aceh Utara Regency) - Hasyem, Muhammad; Larasati, Endang; Suwitri, Sri; Warsono, Hardi (Jurnal Ilmiah Peuradeun, 2022)
Regent Regulation Number 39 of 2017 concerning Procedures for Distribution and Determination of Details of Gampong Funds is prioritized for community development and empowerment. This study aims to describe the implementation of the Aceh Utara Regent's Regulation and analyze the supporting and inhibiting factors in the implementation of the Aceh Utara Regent's Regulation. This study uses a qualitative method with a descriptive analysis approach. The results showed that all gampongs in Syamtalira Bayu sub-district had finished compiling the Village Fund Policy Plan (Qanun APBG) for the current year and reported the realization of the use of the Gampong Fund for the fiscal year; All Village Fund Policy Activities that have been determined (Qanun APBG) have been completed, although there are still villages that are late in completing them; All Gampong Funds have been completed, although reporting is still ongoing. factors that support and hinder the implementation of the bupati's policies include; communication, resources, attitude of implementers, objectives, environment, as well as steps and company policies. Solving this research problem is done by combining the theory of public policy implementation models from Grindle, Van Meter, and Van Horn, as well as the theory of Edward III.